2021
DOI: 10.1055/s-0041-1735280
|View full text |Cite
|
Sign up to set email alerts
|

Lengths of Stay and Discharge Dispositions after Total Knee Arthroplasty: A Comparison of Robotic-Assisted and Manual Techniques

Abstract: As evidence signifies that short-stay total knee arthroplasties (TKA) can be safe options, it is important to identify factors that contribute to early discharge. There is evidence that robotic-assisted TKAs may lead to shorter lengths of postoperative stays. However, this has not been evaluated as the primary outcome of interest in a large-scale population. The purpose of this study was to compare manual and robotic-assisted TKAs with regard to: (1) length of stay (LOS) and (2) discharge dispositions. TKAs pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…Finally, pain scores were significantly lower in the robotic group, and this was found to be correlated predominantly with systemic inflammation. The lower pain levels suggest that robotic TKA could result in faster recovery and a shorter length of stay, as has been reported in larger studies 38-40 . However, we were not able to demonstrate that directly in our relatively small sample.…”
Section: Discussionsupporting
confidence: 63%
“…Finally, pain scores were significantly lower in the robotic group, and this was found to be correlated predominantly with systemic inflammation. The lower pain levels suggest that robotic TKA could result in faster recovery and a shorter length of stay, as has been reported in larger studies 38-40 . However, we were not able to demonstrate that directly in our relatively small sample.…”
Section: Discussionsupporting
confidence: 63%
“…Our findings are rather discordant with previously published studies conducted in the USA, that insinuate benefits of robotic arm assistance. Archer et al 4 reported a significantly higher proportion of patients undergoing RO TKA were discharged home (91.3% vs 87.4%, p < 0.001). Similarly, Hamilton et al 26 showed that more patients in the RO TKA group were discharged home (90.4% vs 79.5%) instead of a subacute rehabilitation facility (9.6% vs 20.5%; 0.051, Pearson chi-squared test and 0.041, Fisher’s exact test).…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in concordance with previous studies. Archer et al 4 retrospectively looked at 10,296 patients undergoing robotic arm-assisted (n = 4,303) or conventional (n = 5,993) TKA, and reported a significantly lower mean LOS in the robotic group (1.68 days, standard deviation (SD) 0.86) compared with the conventional (1.86 days, SD 0.94, p < 0.001). Grosso et al 20 also conducted a large-scale study among 4,086 primary TKAs and reported shorter LOS when robotic arm assistance was used (1.46 vs 1.80 days, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations